The Problem of Sal (Shorea robusta Gaertn.) Regeneration in A3 Dry Peninsular Sal Forests of Bihar - Sahay, B. K. (Indian Forester, 1955)
The problem of sal (Shorea robusta) regeneration in A3 dry peninsular sal forests of Bihar, has been presented along with its growing importance in management. The Recruitment, as well as the Establishment stages of sal regeneration have been discussed in the background of well-known field results. Compaction of the top-soil is indicated to be contended against, for securing recruitment. Soil hoeing and soil working are suggested as interim measures, and the exclusion of forest fires, unrestricted grazing, surface exposure and desiccation, as the long-term measures for loosening the compacted top-soil and preventing the dehydration of the sal seed. Dying back of the sal seedlings in the pre-monsoon period, is stated to take place from March onwards. Moisture and root competition at the peak of the growing season are indicated to be the limiting factors responsible for the dying hack of the whippy sal seedlings. Drastic fellings of the overwood, as well as the underwood, in one stage followed by cutting of the undergrowth for a number of years consecutively, just before the growing season, is suggested for the establishment of the whippy Sal seedlings. The importance of the cultural operations has been emphasized. The elongation of the roots of seedlings is said to be dependent upon its moisture supply by sub-irrigation in the capillary fringe from perched or hanging water-table. The massive vegetation is stated to lower the water-table by transpiration losses. Further soil-moisture is depleted by root-competition. The intensity of root competition in the A horizon is supposed to increase rapidly with the age of the stand. The amount of available soil-moisture may be greatly increased by the elimination of root-competition during periods of moisture stress of the growing season. Studies by various workers seem to confirm the conclusion arrived at in this connection. The elimination of all the transpiring plants seems to be the only remedy for conserving moisture in the period of drought which is also precisely the period of growth of sal seedlings.